STRUKTUR KOMUNITAS TERIPANG (Holothuroidea) DI PERAIRAN PANTAI DESA NAMTABUNG, KECAMATAN SELARU, KABUPATEN KEPULAUAN TANIMBAR - Matrutty, Maria; Wakano, D; Suriani, S (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2021)
Sea cucumber is an invertebrate which is widely used by the community as food and medicine. The purpose of this study is to analyze the community structure of sea cucumber (Holothuroidea) in the coastal waters of Namtabung Village, Selaru District, Tanimbar Islands Regency. The used method to collect sea cucumber samples was the linear quadratic transect method with the number of observation stations as many as three stations, the samples of sea cucumbers obtained will be identified using an identification book. The results showed that there were four species of sea cucumber from the Holothuridea family, genus Holothuria and Bohadschia with the types namely Holothuria scabra, Holothuria edulis, Holothuria atra, and Bohadschia marmorata. Holothuria scabra has the highest density of 0.202 ind / m2. The highest relative abundance was shown by Holothuria edulis at 28.12%. The type of diversity index value is 1.3662 which means moderate diversity, and the dominance index is 0.2533, which means that there are no dominant species. The relative distribution pattern is at Ëƒ 1, which means that the distribution pattern is clustered. The highest index of importance was Holothuria scabra with a value of 91.07%. Overall, the sea cucumber community structure in the coastal waters of Namtabung Village is in the stable category. The highest index of importance was Holothuria scabra with a value of 91.07%. Overall, the community structure of sea cucumber in the coastal waters of Namtabung Village is in the stable category. ABSTRAK Teripang merupakan hewan tidak bertulang belakang yang banyak dimanfaatkan oleh masyarakat sebagai bahan pangan dan obat-obatan. Tujuan dari penelitian ini adalah menganalisis struktur komunitas teripang (Holothuroidea) di perairan pantai Desa Namtabung Kecamatan Selaru, Kabupaten Kepulauan Tanimbar. Metode yang digunakan untuk pengambilan sampe teripang adalah metode transek linear kuadrat dengan jumlah stasiun pengamatan sebanyak tiga stasiun, sampel teripang yang diperoleh akan diidentifikasi menggunakan buku identifikasi. Hasil penelitian menunjukan terdapat empat spesies teripang dari famili Holothuridea, genus Holothuria dan Bohadschia dengan jenis-jenis yaitu Holothuria scabra, Holothuria edulis, Holothuria atra, dan Bohadschia marmorata. Kepadatan tertinggi dimiliki oleh jenis Holothuria scabra sebesar 0,202 ind/m2. Kelimpahan relative tertinggi ditunjukkan oleh Holothuria edulis sebesar 28,12%. jenis Nilai indeks keanekaragaman sebesar 1,3662 yang artinya keanekaragaman sedang, dan indeks dominansi 0,2533 yang artinya tidak terdapat spesies yang mendominansi. Pola penyebaran relatif berada pada angka Ëƒ 1 yang artinya pola sebaran bersifat mengelompok. Indeks nilai penting tertinggi adalah Holothuria scabra dengan nilai 91,07%. Secara keseluruhan, struktur komunitas teripang di daerah perairan pantai Desa Namtabung berada dalam kategori stabil. Kata kunci: Struktur komunitas, teripang, indeks ekologi, Desa Namtabung, Maluku